Meta-analysis of high-flow nasal cannula oxygen therapy versus non-invasive ventilation after invasive mechanical ventilation - Maimaitiniyazi, Mailidan; Yisimitila, Tuersunayi; Maimaitiniyazi, Muyesaier; Maisuti, Meiheliya; Aihaiti, Ailifeire; Chenfei, Zhang; Nijiati, Yilizhati; Nijiati, Muyesai (Frontiers in Medicine, 2025)
ObjectiveTo compare high-flow nasal cannula (HFNC) oxygen therapy and non-invasive ventilation (NIV) for patients after liberation from invasive mechanical ventilation, to assess whether HFNC is better than NIV at improving blood gases [PaO2, PaCO2, and oxygenation index (OI)], reducing re-intubation rates, pulmonary infections, mortality, and shortening the length of stay in intensive care unit (ICU), and to evaluate if HFNC is a feasible alternative to NIV for respiratory support.MethodsThis meta-analysis included randomized controlled trials (RCTs) and non-RCTs (NRCTs) from PubMed, Web of Science, CNKI, and Wanfang for further assessment. Evaluation indexes included PaO2, PaCO2, OI, re-intubation rate, pulmonary infection rate, length of stay in ICU, and mortality rate.ResultsHFNC showed higher PaO2 [MD = 2.95, 95%CI (2.23, 3.67), p < 0.00001], lower PaCO2 [MD = −3.04, 95%CI (−3.56, −2.52), p < 0.00001], higher OI [MD = 10.98, 95%CI (6.52, 15.45), p < 0.00001], lower re-intubation rate [OR = 0.45, 95%CI (0.33, 0.63), p < 0.00001], and shorter length of stay in ICU [MD = −6.15, 95%CI (−6.86, −5.44), p < 0.00001] compared to NIV. Additionally, no significant differences in pulmonary infection rate [OR = 0.57, 95%CI (0.29, 1.11), p = 0.10] or mortality [OR = 1.29, 95%CI (0.96, 1.72), p = 0.09] were observed between HFNC and NIV.ConclusionHFNC can improve PaO2 and OI, reduce PaCO2, re-intubation rate, and length of stay in ICU, with no difference in pulmonary infection or mortality compared to NIV, supporting it as a viable clinical alternative for post-extubation respiratory support.